2010
DOI: 10.1055/s-0029-1245560
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of First Trimester Screening and Early Fetal Anomaly Scan on Invasive Testing Rates in Women with Advanced Maternal Age

Abstract: Increasing numbers of women≥35 years of age rely on the individually adjusted risk figure to make a decision about invasive testing. The application of these selective procedures can reduce the rates of invasive testing with fewer losses of normal fetuses and led to an earlier diagnosis of aneuploidies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
(22 reference statements)
3
11
0
1
Order By: Relevance
“…Also, similarly to international reports which suggest that low socioeconomic status could be a risk factor for CMs (31, 32), with socioeconomic status being determined by mother’s and father’s education level and occupation (32), we found that low education level and being unemployed was associated with significantly increased likelihood of having a baby with CM. We also found that older mother’s age is a risk factor for CMs, similarly to previous results (33, 34, 35). Even though previous reports did find an association between low birth weight and the risk of CMs (36) we did not find such an association even after controlling for a number of variables.…”
Section: Discussionsupporting
confidence: 92%
“…Also, similarly to international reports which suggest that low socioeconomic status could be a risk factor for CMs (31, 32), with socioeconomic status being determined by mother’s and father’s education level and occupation (32), we found that low education level and being unemployed was associated with significantly increased likelihood of having a baby with CM. We also found that older mother’s age is a risk factor for CMs, similarly to previous results (33, 34, 35). Even though previous reports did find an association between low birth weight and the risk of CMs (36) we did not find such an association even after controlling for a number of variables.…”
Section: Discussionsupporting
confidence: 92%
“…This is a well-established finding in the general population 22,24,25. Moreover, according to Chen et al,34 this finding was also observed in the ART population.…”
Section: Discussionsupporting
confidence: 67%
“…Both lower and higher maternal age may pose increased risks for birth defects 1118. For example, older mothers have a higher risk of chromosomal abnormalities,1922 such as Down syndrome,2325 but whether they are at excess risk of nonchromosomal birth defects is less clear 17. It is important to have accurate information on maternal age-specific risks of birth defects after ART to gauge the implications of this rise in maternal age for public health, to gauge clinical care needs, and to provide information to couples of childbearing age 16…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal ultrasound screening is being offered earlier and earlier [9]. Large studies of noninvasive prenatal screening have already indicated that it will lead to a decrease of invasive prenatal screening procedures such as amniocentesis (AC) or chorionic villi biopsy (CVS) [10].…”
Section: Introductionmentioning
confidence: 99%